2014
DOI: 10.1093/treephys/tpu072
|View full text |Cite
|
Sign up to set email alerts
|

Short-term water stress impacts on stomatal, mesophyll and biochemical limitations to photosynthesis differ consistently among tree species from contrasting climates

Abstract: Predicting the large-scale consequences of drought in contrasting environments requires that we understand how drought effects differ among species originating from those environments. A previous meta-analysis of published experiments suggested that the effects of drought on both stomatal and non-stomatal limitations to photosynthesis may vary consistently among species from different hydroclimates. Here, we explicitly tested this hypothesis with two short-term water stress experiments on congeneric mesic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 55 publications
5
121
0
3
Order By: Relevance
“…Instead, a stress factor, which ranges from 0 to 1, is calculated based on the relative moisture content at each soil layer. This factor is applied to stomatal conductance and mesophyll conductance, as well as the maximum RuBisCO activity rate (Vcmax) and maximum electron transport rate (Jmax), in order to account for experimentally observed effects of drought on stomatal and non-stomatal photosynthetic limitation (Zhou et al, 2014). The stress factor (γ ) of water limitation is calculated as…”
Section: Reformulation Of Soil Hydric Stress Above the Permafrost Tablementioning
confidence: 99%
“…Instead, a stress factor, which ranges from 0 to 1, is calculated based on the relative moisture content at each soil layer. This factor is applied to stomatal conductance and mesophyll conductance, as well as the maximum RuBisCO activity rate (Vcmax) and maximum electron transport rate (Jmax), in order to account for experimentally observed effects of drought on stomatal and non-stomatal photosynthetic limitation (Zhou et al, 2014). The stress factor (γ ) of water limitation is calculated as…”
Section: Reformulation Of Soil Hydric Stress Above the Permafrost Tablementioning
confidence: 99%
“…Bonan et al (2014) showed that during drought periods, the formulation of the soil moisture stress scalar was likely to be the cause of error in g s calculations, rather than the g s scheme itself. Zhou et al (2013Zhou et al ( , 2014 demonstrated that the g 1 parameter could be linked to a more theoretical approach to limit gas exchange during water-limited periods, by considering differences in species water use strategies.…”
Section: Optimisation Theory In Lsmsmentioning
confidence: 99%
“…Entre los parámetros fisiológicos más importantes para evaluar la respuesta fisiológica de la planta, se encuentran los de intercambio gaseoso como fotosíntesis y transpiración, fuertemente controlados por factores ambientales como la luz y la temperatura que pueden reducir la asimilación de CO 2 , disminuir la producción de carbohidratos o incluso ocasionar un daño irreversible sobre el aparato fotosintético (Zhou et al, 2014;Stasik y Jones, 2007). La fluorescencia de la clorofila que brinda información sobre el estado del fotosistema II y de la presencia de algún estrés biótico o abiótico en la planta (Baker, 2008;Maxwell y Johnson, 2000), y el potencial hídri-co, además de determinar el estado hídrico de la planta, se identifican los puntos más críticos a lo largo del día y en prealba (Zhou et al, 2014;Eamus et al, 2006).…”
Section: Introductionunclassified
“…La fluorescencia de la clorofila que brinda información sobre el estado del fotosistema II y de la presencia de algún estrés biótico o abiótico en la planta (Baker, 2008;Maxwell y Johnson, 2000), y el potencial hídri-co, además de determinar el estado hídrico de la planta, se identifican los puntos más críticos a lo largo del día y en prealba (Zhou et al, 2014;Eamus et al, 2006).…”
Section: Introductionunclassified